Imperfect compromise : a new consensus among Israelis and Palestinians - Karpin, Michael I. (Potomac Books, 2013)
The Middle East is now in the eye of a storm. But as this storm abates, an opportunity for peace and progress has emerged. In Imperfect Compromise, Michael Karpin, an Israeli broadcast journalist, presents a new thesis about the Middle East peace settlement. He lays out an optimistic forecast: The violent conflict between Arabs and Jews that has had the greatest negative impact on world peace since the end of the Cold War is moving steadily toward resolution. Moreover, since the first Zionists settled on the shore of the Lake of Galilee a hundred years ago, the relations between Arabs and Jew.